Exploring the fatty acid amide hydrolase and cyclooxygenase inhibitory properties of novel amide derivatives of ibuprofen - Alessandro Deplano; Jessica Karlsson; Mona Svensson; Federica Moraca; Bruno Catalanotti; Christopher J. Fowler; Valentina Onnis (Taylor & Francis Group, 2020)
Inhibition of fatty acid amide hydrolase (FAAH) reduces the gastrointestinal damage produced by non-steroidal anti-inflammatory agents such as sulindac and indomethacin in experimental animals, suggesting that a dual-action FAAH-cyclooxygenase (COX) inhibitor could have useful therapeutic properties. Here, we have investigated 12 novel amide analogues of ibuprofen as potential dual-action FAAH/COX inhibitors. N-(3-Bromopyridin-2-yl)−2-(4-isobutylphenyl)propanamide (Ibu-AM68) was found to inhibit the hydrolysis of [3H]anandamide by rat brain homogenates by a reversible, mixed-type mechanism of inhibition with a Ki value of 0.26 µM and an α value of 4.9. At a concentration of 10 µM, the compound did not inhibit the cyclooxygenation of arachidonic acid by either ovine COX-1 or human recombinant COX-2. However, this concentration of Ibu-AM68 greatly reduced the ability of the COX-2 to catalyse the cyclooxygenation of the endocannabinoid 2-arachidonoylglycerol. It is concluded that Ibu-AM68 is a dual-acting FAAH/substrate-selective COX inhibitor.